2016
DOI: 10.1371/journal.pone.0157153
|View full text |Cite
|
Sign up to set email alerts
|

Natalizumab Therapy Modulates miR-155, miR-26a and Proinflammatory Cytokine Expression in MS Patients

Abstract: MicroRNAs fine-tune the regulation of Th1/Th17 lymphocyte subsets in multiple sclerosis. We investigated the expression of miRNAs (previously associated with mycobacterial and viral infections) in MS patients and healthy donors (HD) following 6 months natalizumab therapy. In addition, Th1/Th17 cytokines and the presence of anti-EBNA1/VCA IgG in MS patients with different pattern of miRNA expression have been evaluated. MiR-155, miR-26a, miR-132, miR-146a and Th1/Th17 cytokines expression was detected by RT-rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 35 publications
0
37
0
Order By: Relevance
“…Thus, assaying miRNAs from PBMCs and sera indicate not only the overall inflammatory state but also specify whether the immune system is acting in a beneficial or pathogenic manner. miR-155, which promotes pathogenic helper T cell and pro-inflammatory myeloid cell activation, is elevated during relapse and responds to disease-modifying therapy (DMT) (28). …”
Section: Biomarkers For Ms Relapsementioning
confidence: 99%
“…Thus, assaying miRNAs from PBMCs and sera indicate not only the overall inflammatory state but also specify whether the immune system is acting in a beneficial or pathogenic manner. miR-155, which promotes pathogenic helper T cell and pro-inflammatory myeloid cell activation, is elevated during relapse and responds to disease-modifying therapy (DMT) (28). …”
Section: Biomarkers For Ms Relapsementioning
confidence: 99%
“…[160][161][162][163]166 Current therapeutic approaches exert a notable impact on some of the miRNAs associated with MS. FDA-approved drugs have shown their efficiency in regulating some of the known MS-associated miRNAs, namely, miR-146a, miR-155, miR-145, miR-20a, miR-22, miR-320b, miR-146a, miR-23a, miR-223, miR-BART3-5p, and EBV-miR-BART11 -5p. 132,145,[170][171][172]175,177,178,259 However, in the future, novel approaches need to focus on designing drugs that modulate the miRNA networks as a target. This approach may need more time, expense, and research, but could provide a better life for these patients.…”
Section: Resultsmentioning
confidence: 99%
“…138 Besides, Mameli et al reported that natalizumab could downregulate miR-155 and miR-26a, miRNAs that had previously proven to increase MS pathogenicity (Tables 2 and 5). 130,145,177 Dimethyl fumarate (DMF), another FDA-approved MS treatment drug, has similarly shown efficacy in reducing the expression of the pathogenic miR-155 ( Table 5). 178 Fingolimod (FGM), also FDA-approved MS drug, proved to significantly reverse the aberrant miR-15b, miR-23a, and miR-223 expression after 6 months of the administration.…”
Section: Data Extractionmentioning
confidence: 99%
“…In addition, in the animal model of MS (experimental autoimmune encephalomyelitis, EAE), genetic deletion of the miRNA cluster miR-106a∼363 (containing Natalizumab-regulated miR-20b) resulted in a more severe disease course, and it upregulated in vivo the miR-20b target genes [89]. In addition, the treatment with Natalizumab restored the expression levels of miR-26a and miR-155 [90], which were upregulated in PBMCs of MS patients, as well as in urine exosome, plasma, and in the spinal cord samples from EAE mice [82]. Notably, miR-155 plays a central role in many processes involved in the pathogenesis of MS, such as immune cell activation, neurodegeneration and permeabilization of the BBB [18].…”
Section: Multiple Sclerosismentioning
confidence: 99%